The Picture of Sustainable Development in “Problemy Ekorozwoju/Problems of Sustainable Development” Journal - Fiut, Ignacy S. (Problemy Ekorozwoju, 2011)
The paper includes presentation and discussion of the results of empirical studies (content analysis) carried out by analysis of the density transfer of the materials published in scientific journal “Problemy Ekorozwoju/ Problems of Sustainable Development” (PoSD). During five years of appearance of this title, 10 numbers were published, which included 166 texts. The aim of the analysis was to trace the forms of understanding the category of sustainable development (SD), so how authors explain, understand and use it in the broader contexts of scientific materials published in this journal. The presented results can be characterized by some regularity. Editors above all publish articles. Reviews or information are rare, there are no interviews and open polemics. Discussions about similar research-related phenomena of SD in Europe and worldwide are seldom. Editors often publish works of national authors from academic environment, also publications of researchers mainly from the USA, writing papers in English and Polish-English, are quite frequent. Published articles, in major parts, are the size of one or half sheet and are rarely illustrated. However, the vast proportion of them, almost 95% of the issues, relate to SD. Analysis of the SD category in almost 30% are focused primarily on issues of philosophy, and is followed by economic, social, political and environmental discussions. In the opinion of researchers, SD is necessary for the maintenance of social and natural safety of human life on Earth. Most authors use the broader concept of SD, indicating the dynamic nature, which manifests itself in a self-sustainable and the durable processes. This category, according to their opinions, is integrating many phenomena of natural and social nature, and above all it must have not only global, but also nationwide dimension.